Paediatric antiretroviral overdose: A case report from a resource-poor area - Bryan A. Ogoti; Angela A. Otedo; Thomas M. Chokwe (AOSIS, 2020)
Introduction: Toxic side effects from antiretroviral overdose in children have not been widely reported. Antiretroviral drugs are widely used as oral medications throughout sub-Saharan Africa. Patient presentation: We describe the clinical presentation and management of a 3-year-old male in rural Kenya, who accidentally overdosed on abacavir/lamivudine combination pills. The number of pills taken was approximately 250 tablets, that is 15 g of abacavir and 7.5 g of lamivudine. He presented 24 hours later to Homabay County Referral Hospital, with unresponsiveness, inability to feed and absence of playfulness. Physical examination revealed a sick-looking, 'unconscious' child, responding only to voice, with tachycardia, hypertension and moderate dehydration. Management and outcome: He was managed conservatively with rehydration, namely intravenous 1125 mL of 5% dextrose in 0.9% saline, and the monitoring of his neurologic status, urine output and all vital signs. He regained normal neurological function after 24 hours, and recovered uneventfully, but was lost to follow-up. Conclusion: In an area endemic for HIV and where antiretroviral drug use is commonplace, there is a need for health education to ensure that parents keep drugs out of the reach of children. In the case of a suspected overdose, parents need to be reminded to seek medical attention immediately. Physician awareness of the clinical presentation, management and challenges with an antiretroviral drug overdose is also important.